Konsep Tri Murti Dalam Teks Tutur Aji Sasaraswati - Ni Wayan Suantini (Jnanasiddhanta : Jurnal Teologi Hindu, 2023)
The text of Aji Saraswati's speech is a vehicle for storing the cultural heritage of the Balinese people. This text belongs to the Siwaistis text and inspires the diversity of Hindus in Bali. Few know the contribution of this manuscript to the formation of civilization and the various teachings stored in it. The various teachings contained therein are the result of contemplation of habits, thoughts, literature and values passed down from generation to generation. This acts like a compass in providing guidance for all situations that may arise at any time. Both in individual life and in collective life (society). In the speech text, Aji Saraswati explains about the fundamental role of Tri Murti. Tri Murti consists of Lord Brahma as the creator god (utpeti), Lord Wisnu as the guardian god (Sthiti) and Lord Siwa as the god of fusion (pralina). Keywords: Tri Murti, Utpeti, Sthiti, Pralina